Determinants for the practice of caesarian section: A case-control study (Portuguese Journal of Family Medicine and General Practice, 2013)
Objectives: To determine if years of maternal education, body mass index (BMI), smoking, nulliparity, follow-up of pregnancy in the private sector, previous cesarean section (C-section), diabetes, hypertension and large birth weight are associated with increased risk for having a C-section, to test the association between C-section and postpartum complications (hemorrhage, infection and readmission), the association between C-section and breastfeeding at discharge and to describe the indications for C-section. Study design: Case control study Setting: Leiria-Pombal Hospital Centre. Participants: A random, stratified, non-proportional sample of 400 women (200 with C-section and 200 with vaginal delivery) giving birth in the Leiria-Pombal Hospital in 2010 was selected. Methods: Tests of association between variables and the type of delivery was done by bivariate analysis with calculation of the odds-ratio, using the Chi-square test with significance set at the 0.05 level. Results: The rate of C-sections increased the with the level of maternal education (p < 0,001). In the C-section group, the rate of nulliparity was 57,0% (p = 0,002). Among multiparous women undergoing a C-section 87,7% had a previous C-section (p < 0,001). In the C-section group a higher rate was found of hypertension (72,4%, p = 0,012) and of follow-up of pregnancy in the private sector (56,9%, p = 0,002). Infants receiving formula (81%) and infants receiving mixed formula and breast feeding at hospital discharge (58,5%) were more likely to have been delivered by C-section (p = 0,005). When infection complicated delivery, this was most often after C-section (88,9%, p = 0,001). Statistical significant associations were not found between C-section and BMI, smoking, large birth weight, and diabetes. Conclusions: Higher maternal educational level, nulliparity, follow-up of pregnancy in the private sector, previous C-section, hypertension, the use of formula at discharge, and post-partum infection were association with C-section.
Keywords: Cesarean section; Obstetric Delivery; Prevalence